2009
DOI: 10.1021/jp810720t
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Characterization, and Double Layer Capacitance Charging of Nanoclusters Protected by 6-Mercaptopurine

Abstract: The synthesis of gold nanoparticles by using the one-phase method of Brust has been carried out in this work to obtain 6-mercaptopurine monolayer protected gold nanoclusters (6MP-MPCs). The 6MP-MPCs are somewhat polar clusters that are soluble in polar solvents such as DMF and DMSO and in neutral and alkaline aqueous solutions. The average size of the clusters is 2.4 ( 0.5 nm and a stoichiometry of Au 459 (6MP) 62 has been established by taking into account high resolution transmission electron microscopy, X-r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(40 citation statements)
references
References 68 publications
2
37
0
1
Order By: Relevance
“…For alkanethiols with polar end groups, however, e.g., 6-mercaptopurine (6MP) on small, Au 459 (6MP) 62 , nanoparticles in water, a footprint of 29 Å 2 is obtained. 53 Hence, the 21.3 Å 2 value obtained for 11-MU is consistent with both the polar nature of this alkanethiolate ligand and the size and less acute surface curvature of the 13.8 nm Au NPs used in the present work.…”
Section: Resultssupporting
confidence: 85%
“…For alkanethiols with polar end groups, however, e.g., 6-mercaptopurine (6MP) on small, Au 459 (6MP) 62 , nanoparticles in water, a footprint of 29 Å 2 is obtained. 53 Hence, the 21.3 Å 2 value obtained for 11-MU is consistent with both the polar nature of this alkanethiolate ligand and the size and less acute surface curvature of the 13.8 nm Au NPs used in the present work.…”
Section: Resultssupporting
confidence: 85%
“…In order to further check if the instability of the LYZ–AuNP bioconjugates depends on the binding characteristics of the protein on the nanoparticle surface, AuNPs protected by organic monolayers of different chemical nature have been used. The 6MP-AuNPs have been shown to be stable in alkaline media due to the negative charges of the 6MP molecules that show a dissociation p K a at pH around 6. , These molecules are covalently bound to the nanoparticle surface, and consequently, they are not displaced by the proteins upon bioconjugation. The pH–titration results of 6MP-AuNPs in the presence of 200 nM LYZ are shown in Figure b.…”
Section: Resultsmentioning
confidence: 99%
“…3,10 6-Mercaptopurine (6MP) has interest from the point of view of its applications in leukemia treatment 11 and therefore has been immobilized on gold nanoparticles with drug delivery purposes. [12][13][14][15] A few groups have studied 6MP SAMs on Au(111), [16][17][18][19][20] on Ag 21,22 and Hg 18,19 surfaces. In all cases, it has been reported that the molecule adsorbs through the S atom.…”
Section: Introductionmentioning
confidence: 99%